Socio-Economic Life and Survival Strategies of Impoverished Widows in West Muna Regency - Jamiludin, Jamiludin; Hamiru, La Ode; Bauto, La Ode Monto (Universitas Negeri Semarang, 2023)
This study aims to describe and analyse (1) the socio-economic life of poor widows and the performance of family functions by poor widows in the Napano Kusambi District of the West Muna Regency, (2) the causes of poverty in widowed women, and (3) survival strategies for poor widows to escape the poverty trap. This type of research employs a qualitative, descriptive methodology. Implementing a qualitative description method enables researchers to provide a more thorough and in-depth explanation of the field’s case descriptions. Three months of investigation were conducted in the Napano Kusambu District of the West Muna Regency between December 2022 and February 2023. The result of this study showed that (1) the phenomenon of socio-economic life of widows in Napano Kusambi District can be observed in their increasing household roles, increasing economic problems, and increasing responsibilities within the family, as well as their performing family functions in the form of economic functions, religious functions, cultural functions, the function of love, and the function of protection. (2) The causes of widows’ poverty include limited land ownership and access to production, a lack of capital for businesses, and low levels of education and work skills. (3) The widow’s survival strategies include an active strategy, a passive strategy, and a network strategy.